Surgical Strategies for Siewert Type II Esophagogastric Junction Carcinomas: A Randomized Controlled Trial - Tao, Kai; Dong, Jianhong; He, Songbing; Xu, Yingying; Yang, Fan; Han, Guolin; Abe, Masanobu; Zong, Liang (Frontiers in Oncology, 2022)
Aim To determine the ideal surgical approach for Siewert type II EGJ carcinomas. Methods We conducted the randomized controlled trial (RCT) at Shanxi Cancer Hospital from January 2014 to August 2016. A total of 105 patients with T1-4N1-3M0 Siewert type II EGJ carcinomas were initially recruited. The final follow-up was up to June 30, 2019. Patients were randomized to undergo either a proximal gastrectomy plus jejunal interposition (PG+JI), proximal gastrectomy plus esophagogastrostomy (PG+EG), or total gastrectomy plus Roux-en-Y esophagojejunostomy (TG+RY). The primary endpoint was postoperative complications. Secondary endpoints were 5-year survival and recovery indexes. Results Among 105 patients, 100 patients (95.2%; mean age, 56.2 years) with tumors <3cm in size underwent surgery: PG+JI (n=33) vs. PG+EG (n=33) and TG+RY (n=34); 91 patients completed the study. Among the groups, the PG+JI group had the longest reconstruction time: 34.11 ± 6.10 min vs. 21.97 ± 3.30 min (PG+EG) vs. 30.56 ± 4.26 min (TG+RY); p<0.001. There was no postoperative mortality. In the per-protocol analysis, the PG+JI group showed a decreased tendency in complication rate: 6.9% vs. 23.3% (PG+EG) vs. 18.8% (TG+RY), but there was no significant difference. For recovery indexes, the TG+RY group had the lowest values of the amount of single meal, weight loss, hemoglobin, albumin, pepsin, and gastrin among the three groups. There was no significant difference among the three groups in 5-year survival. Conclusions Proximal gastrectomy is preferable for T1-4N1-3M0 Siewert type II EGJ carcinomas with tumors <3cm in size because of its better nutrition status under similar postoperative complication to total gastrectomy. Jejunal interposition can be recommended as a optional reconstruction approach after proximal gastrectomy. Clinical Trial Registration https://www.chictr.org.cn/, identifier ChiCTR-IIR-16007733.